1998
DOI: 10.1002/hep.510270223
|View full text |Cite
|
Sign up to set email alerts
|

The portal lobule in rat liver fibrosis: A re-evaluation of the liver unit

Abstract: We re-evaluated three schemes of liver organization: the classic lobule, the portal lobule, and Rappaport's liver acinus. The lobular angioarchitecture of normal rat liver and the three-dimensional structure of pseudolubules found in rat livers with fibrosis induced by swine serum were compared with the classic lobule of the pig.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 21 publications
1
19
0
1
Order By: Relevance
“…The terminal branch(es) of portal veins can be demonstrated inside larger foci, and the central veins are pushed aside. This is not surprising, considering that others 22,23 and we demonstrated that the foci are the descendant of canals of Hering-derived oval cells, which are always arranged in a radial fashion around the portal tracts. It seems that oval cells preserving their original periportal position and connections transform into small hepatocytes and constitute the foci.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The terminal branch(es) of portal veins can be demonstrated inside larger foci, and the central veins are pushed aside. This is not surprising, considering that others 22,23 and we demonstrated that the foci are the descendant of canals of Hering-derived oval cells, which are always arranged in a radial fashion around the portal tracts. It seems that oval cells preserving their original periportal position and connections transform into small hepatocytes and constitute the foci.…”
Section: Discussionsupporting
confidence: 75%
“…Though the classical lobule is organized around a central vein and the portal branches are at the periphery, a fully developed focus is more similar to the so-called portal lobule. 22 It should be kept in mind that the healthy liver lobule is demarcated by approximately six portal tracts. Thereby, an individual focus does not turn into a hepatic lobule, but more foci can contribute to the build-up of a regenerated liver lobule.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using dye injections into portal and hepatic veins of rat liver suggest that the structural/functional unit of the rat liver is the portal lobule [21]. The difficulty with this model is that according to angioarchitectural studies, a considerably larger portion of the blood supply to rat liver sinusoids originates from the portal venous branch.…”
Section: Discussionmentioning
confidence: 99%
“…28 These studies yielded interesting but very contradictory data, and none was able to visualize Rappaport's liver acinus. Instead, different types of parenchymal units were newly introduced or revisited, such as the portal lobule, 29 so called "cone-shaped primary lobules", 6-8 of which form a classical (central-vein) but secondary lobule according to Matsumoto,12,13 or "primary lobular units" and "liver modules" with differences to, but basically the same organization as the classic (central vein) liver lobule. 10,11 Using a specific experimental model based on the lownumber intrahepatic portal-embolic transplantation of endocrine tissues it took about 50 years to prove the correctness of RappaportЈs acinus model since his first description in 1954.…”
Section: Discussionmentioning
confidence: 99%